Pengaruh Motivasi, Disiplin Kerja dan Tunjangan Kerja terhadap Kinerja Pegawai Kecamatan Gondang Kabupaten Tulungagung - Purwati, Purwati; Mulyaningtiyas, Ratna Dewi (Universitas Islam Kadiri, 2024)
This research aims to: Analyzing the simultaneous significant influence of motivation, work dicipline, and job benefit on employee performance ;examining impact motivation on employee performance ; assesing the influence of job benefitson employee performance This research uses Descriptive Quantitative. the population in this research is in the Gondang Subdistrict, Tulungagung Regency. The researcher does not specify a sample, because all members of the population will be examined. The technique is a method of data collection now. In this study, researchers used the software (software), Microsoft Office Excel 2007 to carry out a descriptive and statistical analysis software (software) Statistical Package for Social Sciences (SPSS) for Windows version 21.0 to carry out the test, test the classical, hypothesis testing and multiple linear regression analysis, , The research findings indicate a significant influence betwen the variables of motivation, work dicipline and job benefits on employee performance . meanwhile the most dominant influencingvariable is the work discipline